Corporate Communication In The Digital Era: Challenges And Opportunities For PT Binajasa Abadikarya - Ricky Suzano (Syntax Idea)
The digital era has significantly transformed corporate communication, presenting both challenges and opportunities for organizations. PT Binajasa Abadikarya, a leading manpower and outsourcing services provider in Indonesia, is no exception to these changes. This research aims to explore the challenges PT Binajasa Abadikarya faces in maintaining effective corporate communication and to identify the opportunities available to enhance its communication strategies in the digital age. The study employs a descriptive qualitative research method, using primary data collected through interviews with key stakeholders within the company, and secondary data sourced from relevant articles, journals, and books. Data analysis was conducted using NVivo software to systematically organize and interpret the qualitative data. The findings reveal that PT Binajasa Abadikarya faces significant challenges, including maintaining consistency in messaging across digital platforms, managing crisis communication in real-time, and overcoming content saturation. However, the research also identifies substantial opportunities for the company, such as leveraging digital tools for broader stakeholder engagement, utilizing data analytics for personalized communication, and implementing an omnichannel communication strategy. These insights provide PT Binajasa Abadikarya with strategic directions to enhance its corporate communication and maintain its competitive edge in the digital era